2006
DOI: 10.1158/1055-9965.epi-06-0578
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Cytologic Intrarater and Interrater Reproducibility: the Case of Ductal Lavage

Abstract: The reproducibility of a test result is a critical component of its clinical utility. Little information is available concerning the intrarater reproducibility of cytologic assessments. This study evaluated the reproducibility of cytologic interpretation of epithelial cells obtained from ductal lavage (DL), a minimally invasive method used to obtain sample cells from breast tissue. Two cytospin slides were made for each duct sampled. Slides with <10 cells were considered inadequate to make a diagnosis; the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…Together, our findings confirm and extend previous results from smaller studies [11][12][13], and show that (1) an initial finding of mild atypia is not reproducible on second lavage at intervals ranging from 2 to 14 months, and (2) a significant minority of women (about 20%) may convert from benign cytology at baseline to mild atypia at the repeat procedure. Among other problematic issues with the use of cytologic diagnosis as a biomarker, these findings raise concerns regarding single arm trial designs, where randomized placebo controls are not included.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Together, our findings confirm and extend previous results from smaller studies [11][12][13], and show that (1) an initial finding of mild atypia is not reproducible on second lavage at intervals ranging from 2 to 14 months, and (2) a significant minority of women (about 20%) may convert from benign cytology at baseline to mild atypia at the repeat procedure. Among other problematic issues with the use of cytologic diagnosis as a biomarker, these findings raise concerns regarding single arm trial designs, where randomized placebo controls are not included.…”
Section: Discussionsupporting
confidence: 89%
“…Because the cytologic diagnoses of benign and mild atypia have a subjective component, we included a blinded review of cytological findings by an expert reference cytopathologist (SM) in our study design. This analysis showed a higher concordance between observers (kappa statistic of 0.62) than in previous studies [13,14], possibly because of our higher threshold for sample adequacy (100 rather than 10 epithelial cells). Nevertheless, of the 51 samples with discordant results between cytopathologists (nonbolded boxes of Table 4), 31 or 60% involved discrepancies in the reading of benign and mildly atypical samples.…”
Section: Discussioncontrasting
confidence: 50%
“…Similar results were documented in a pre-mastectomy DL study 19 where mild atypia constituted one-third of samples and was the most challenging and least reproducible diagnostic category. In another study of DL reproducibility, 14/69 women entered into the study underwent two DL procedures and the reproducibility of cellularity and cytology was very similar to that observed in our study 20.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the fair cytologic reproducibility observed can be partly explained by poor intra-rater agreement (j = 0.60 F 0.11), which was subsequently identified when all abnormal slides and random samples of normal slides were re-reviewed (16). Cytologic reproducibility was low for benign, mildly atypical, and markedly atypical cells.…”
Section: Discussionmentioning
confidence: 60%